Evaluasi Program Kelompok Bermain (Playgroup) di Pendidikan Anak Usia Dini (PAUD) Abdi Pertiwi - Inarotul Wahdiyah; Zakky Ansori; Khairunnisa Tanjung; Andini Hania Pratiwi (Peneliti.net, 2022)
Early childhood is a golden age in child development, where all aspects of existing development can be easily absorbed or stimulated by children. Thus PKBM Abdi Pertiwi can improve performance and can make good decisions to support this Playgroup organizing program. The research objective of this program is to assess the success of the activities carried out specifically and see the benefits of the program's activities in this Playgroup. The method used in this study is a qualitative method based on the CIPP Program Evaluation model (Context, Input, Process, Product Evaluation). The result is that PKBM Abdi Pertiwi can improve performance and can make good decisions to support the Playgroup program in the following years so that it can run effectively and efficiently with maximum results.